Assessment of health, environmental and economic impact from waste landfilling and segregation practice in Malaysia - Rangga, Josfirin Uding (2020)
Malaysians disposed of 80 to 90% of their waste in landfills. Health, environmental and economic problems are well known linked to landfills. Thus, Malaysia has implemented the waste segregation at source programme under Act 672 since 2015. Objective: To assess health, environmental, and economic impact from waste landfilling and segregation practice from 2014-2018 in eight (8) states in Malaysia. Methodology: The study areas covered the states under Act 672 (Kuala Lumpur, Putrajaya, Pahang, Perlis, Kedah, Negeri Sembilan, Malacca, and Johor). The available data of solid waste (tonnes) were obtained from the Solid Waste and Public Cleansing Corporation (SWCorp) and Alam Flora Sdn. Bhd. The mathematical models were used to analyse the data of landfilled and segregated domestic waste. Greenhouse gas (GHG) emissions were estimated using the Intergovernmental Panel on Climate Change (IPCC) methodology. Leachate volume and heavy metals were estimated using adopted mathematical models from the Ministry of Housing and Local Government (KPKT) and Emission Estimation Technique Manual. Gerard mathematical models 1998 were used to estimate the land area required for waste disposal in landfills. Non-methane volatile organic compound (NMVOC) emissions and health risks were analysed using the mathematical models of Air Pollutant Emission Factors and the United States Environmental Protection Agency (U.S EPA). Waste management cost and profits were calculated using the adopted equations form literature review and KPKT. Results: There was a significant difference in the volume of collected waste between the states (p-value <0.001) where the highest volume of collected waste was Johor (967 thousand tonnes per year (t/yr.)). The segregation rate was recorded at 0.06% only and 99.94% of domestic waste was dumped in the landfills. The landfilled domestic waste emitted about 109 thousand t/yr. of methane (CH4), equivalent to 2.74 million (M) t/yr. of carbon dioxide (CO2-eq). About 68.65 t/yr. of CH4 (equivalent to 1.72k t/yr. of CO2) were potentially avoided by the waste segregation activity. Waste landfilling generated 565k m3/yr. of leachate in which the segregated waste avoided 354 m3/yr. of leachate production and heavy metals (5.32 x10-3 to 7.09 x10-4 kg yearly). About 32.08 ha/yr. of the land area were used for waste disposal in landfills. The waste segregation practice avoided the use of landfill area about 20.10 ha/yr. There was an acceptable health risk exposure to NMVOC with the value of Hazard Quotient (HQ) <1 and Lifetime Cancer Risk (LCR) <1.0E-04. Overall, the country spent 426 million MYR/yr. for landfilling practice in which 267 thousand MYR/yr. was saved by waste segregation practice. The country could generate the revenues from the electricity selling (43 thousand MYR/yr.) or carbon credits (176 million MYR/yr.) through landfill gas recovery and the selling of recyclable (530 thousand MYR/yr.). Conclusion: Segregation practice potentially reduced GHG emissions, leachate production, land use, health risks and waste management cost. It may generate high revenue through energy production, carbon credit and recyclable selling.